APPLICATION OF PEER TUTORING LEARNING TO IMPROVE LEARNING MOTIVATION AND QUR'AN READING ABILITY IN GRADE X OTKP STUDENTS OF SMK NEGERI 4 BONE - sulaeman sulaeman (Acceleration: Multidisciplinary Research Journal, 2023)
The purpose of this study is to determine students' ability in reading the Qur'an and to enhance students' learning motivation in the subject of Islamic Education through the peer tutoring method, where learning occurs cooperatively and with mutual respect and understanding between students and teachers who work together. The research was conducted in Grade X OTKP of SMK Negeri 4 Bone. The problem identified by the researcher is that the Islamic Education learning process is not optimal due to the limited number of instructional hours, which amounts to 3 hours per week, and the learning is conducted 50% online and 50% offline due to the spread of the COVID-19 pandemic, resulting in a different learning process compared to before. The research conducted in this study is Classroom Action Research (CAR). The sampling technique used is saturated sampling, where the population serves as the sample, consisting of 21 students. Data collection techniques include both test and non-test instruments.